Changing Trends of Consumers' Online Buying Behavior During COVID-19 Pandemic With Moderating Role of Payment Mode and Gender - Sajid, Sana; Rashid, Rao Muhammad; Haider, Waleej (Frontiers in Psychology, 2022)
It was not long ago when technological emergence fundamentally changed the landscape of global businesses. Following that, business operations started shifting away from traditional to advance digitalized processes. These digitalized processes gave further boost to e-commerce industry, making online environment more competitive. Despite the growth trend, there has always been a consumer market that is not involved in online shopping, and this gap is huge when it comes to consumers from developing countries specifically Pakistan. On contrary, recent Covid-19 pandemic has brought drastic changes the way consumers used to intend and behave for digitalized solutions in pre Covid-19 times. Evidence shows that global e-commerce industry has touched phenomenal growth during Covid-19. Whereas Pakistan’s e-commerce industry still holds huge potential and has not fully boomed yet. These facts pave new avenues for marketers to cater to this consumer market for the long-term growth. Hence, the study provides insights of how consumers’ online buying behaviour has transformed during Covid-19 pandemic in the context of Pakistan. Study presents a framework based on the Technology Acceptance (TAM) and Theory of planned behaviour (TPB). Furthermore, moderating role of Gender and Payment Mode has also been examined. For the analysis of variables, Partial least squares (PLS) method has been used to conduct structural equation modelling (SEM) by collecting data from 266 respondents. Results show the significant and positive impact of Perceived Benefits, Perceived Ease of Use, Perceived Enjoyment and Social Influence on Consumers’ intention. Whereas it shows insignificant impact of Gender and Payment Mode as a moderating variable on PEOUBI and BI AB respectively. Results are of utmost significance for Pakistani businesses, marketers, and e-traders to streamline their business practices accordingly. Lastly, proposed framework demonstrates new directions for future research to work upon.